The Perceptions of Nurses and Nursing Students Regarding Family Involvement in the Care of Hospitalized Adult Patients - Faygah M. Shibily; Nada S. Aljohani; Yara M. Aljefri; Aisha S. Almutairi; Wassaif Z. Almutairi; Mashael A. Alhallafi; Fatmah Alsharif; Wedad Almutairi; Hanan Badr (MDPI AG, 2021)
Over the past few decades, there have been concerns regarding the humanization of healthcare and the involvement of family members in patients' hospital care. The attitudes of hospitals toward welcoming families in this respect have improved. In Arab culture, the main core of society is considered to be the family, not the individual. The objective behind involving family in patient care is to meet patients' support needs. Consequently, this involvement affects nurses and their attitudes toward the importance of family involvement in patient care. Objectives: To describe nurses' and nursing students' perceptions of family involvement in the care of hospitalized adult patients in Saudi Arabia. Design: This study used a quantitative descriptive cross-sectional design. The data were collected using a convenience sampling survey via social media. Results: A total of 270 participants (staff and students) took part in this study, including 232 (85.9%) females and 38 (14.1%) males. Moreover, a high percentage of participants (78.8%) acknowledged that family presence strongly affected the improvement of the patient's condition. However, 69.3% of participants thought that involving family members during special care processes or cardiopulmonary resuscitation (CPR) would be traumatizing for these individuals. Moreover, there was a significant diffidence between the attitudes of the nurses and nursing students toward family involvement and the number of years of employment (F = 3.60, p < 0.05). On the contrary, there were insignificant differences between the attitudes of the nurses and nursing students toward family involvement and their gender, nationality, age, education level, and years of work experience in Saudi Arabia (p > 0.05). Furthermore, the regression analysis showed a significant negative correlation between nurses' years of employment and their support of family involvement in patient care (ß = −0.20, SE = 0.08, t = −2.70, p = 0.01). Conclusions: Nurses with more experience showed no support for family involvement in patient care. We have to consider the clinical barriers that affect nurses' support for family involvement in patient-centered care, such as hospital polices, guidelines, and the model used for family-centered care integration in the hospital system to facilitate the interaction between healthcare providers and family members.